Viability and sustainability of desalinating produced water in the oil and gas industry - Grauberger, Brandi M., author; Bandhauer, Todd M., advisor; Tong, Tiezheng, advisor; Sharvelle, Sybil, committee member; Quinn, Jason C., committee member (Colorado State University. Libraries, 2025)
Unconventional oil and gas extraction consumes considerable amounts of water, with up to 11 million gallons of freshwater used for the fracturing of a single well. Millions of gallons can come back to the surface of a well as flowback and produced waters, which are collected and disposed of through deep well injection. Water reallocation and reduction of resource waste can be aided by treating produced water from these operations but is rarely practiced. In particular, treating produced water to zero-liquid-discharge allows for management of dry wastes and generates a clean water source as its only other product. Eliminating the disposal of brines from produced water management would eliminate the need for deep well injection, which has shown to be an unsustainable option for produced water management. A major barrier to produced water treatment is the cost and availability of energy for treatment. Other barriers arise from an incomplete understanding of the system. Specifically, environmental and social impacts of produced water treatment are not understood. For example, it is not known if the discharge of treated produced water will have a negative effect on drinking water supplies or flow of rivers and streams. Without solving these challenges, produced water will continue to be disposed into injection wells, wasting the potential to reduce freshwater consumption, and further threatening seismic stability and access to freshwater reserves in oil and gas producing regions. This work completes three major analyses to understand the potential of produced water desalination. First, the accessibility of waste heat from the oil and gas industry, which is limited due to spatial and temporal disparities in waste heat and produced water production, was quantified and compared to energy requirements for produced water treatment. The results show that there is potential for waste heat utilization by membrane distillation, a thermal-membrane desalination technology option, in the oil and gas industry for produced water desalination with appropriate waste heat storage system integrations. The next major evaluation is of the economic and environmental impacts for multiple zero liquid discharge desalination options. Economic results show that the existing technology of mechanical vapor compression is difficult to reliably challenge, in terms of cost. However, environmental emissions can be much improved when using waste heat as an energy source for desalination or when treating with electrodialytic crystallization. Finally, this work evaluates options for zero liquid discharge desalination in the oil and gas industry using a triple bottom line sustainability framework. This framework considers the economic, environmental, and social competitiveness of technologies in multiple stakeholder-preference scenarios, which weight the importance of the three categories in different ratios. Results show that the use of waste heat is paramount to the consideration of membrane distillation as a technology option in the oil and gas industry. Further results show that the comprehensive consideration of economic, environment, and social impacts provide context to overall fit of technology options in the oil and gas industry. More detail of each major objective of this work are shared in the following paragraphs. The use of waste heat has been proposed to reduce the energy footprint of membrane distillation for flowback and produced water treatment. However, its feasibility has not been fully understood for produced water treatment. Accordingly, the third chapter of this work performed systematic assessments through thermodynamic modelling of waste heat capture, storage, and transportation for decentralized produced water treatment at well pads located in the Denver-Julesburg Basin. A wide range of sensible, phase-change, and thermo-chemical storage materials were assessed for their effectiveness at the utilization of waste heat from on-site hydraulic fracturing engines and natural gas compressor stations, in order to overcome the temporal or spatial mismatch between waste heat availability and produced water generation. Results show that the type of storage material being used can have a high impact on the efficiency of waste heat utilization and the treatment capacity of membrane distillation. Sensible storage materials only utilize sensible heat capacities, while phase-change materials have improved performance because they are able to additionally store latent heat. However, sensible and phase-change storage materials lose 11–83% of heat due to conversion inefficiencies caused by their changing temperatures. Thermo-chemical materials, on the other hand, have the highest potential for use because they collect and release heat at constant temperatures. Three thermo-chemical storage materials (magnesium sulfate, magnesium chloride, and calcium sulfate) were identified as those with the best efficiencies due to their elevated discharge temperatures which reduce the energy consumption of membrane distillation. In addition, these materials have high volumetric energy storage density, which enables capture and transportation of waste heat from remote locations such as natural gas compressor stations to the well sites, yielding up to 70% reduction in transportation costs relative to moving produced water to centralized treatment facilities at natural gas compressor stations. The third chapter of this work demonstrates the importance of selecting appropriate energy storage material for leveraging low-grade thermal energy such as waste heat to power membrane distillation for decentralized wastewater treatment. With more certainty given in the possibility and logistics of using waste heat for the membrane distillation system in the oil and gas industry, further analysis was needed to evaluate new technologies with existing brine desalination technologies in terms of replacement potential. Four technologies were considered: mechanical vapor compression with a crystallizer, electrodialytic crystallization, membrane distillation with a crystallizer using electrical heating, and membrane distillation with a crystallizer using waste heat. The fourth chapter of this work evaluates the economic and environmental competitiveness of said technologies. Zero liquid discharge desalination has garnered considerable attention for its potential to mitigate the impact of water scarcity while minimizing environmental consequences associated with ill-managed brine wastes. In the fourth chapter of this work, the economic and environmental competitiveness of an electrodialytic crystallization system designed in recent works was evaluated. It was found that when compared to existing zero liquid discharge technologies, electrodialytic crystallization could compete economically with the potential to reduce costs of zero liquid discharge by over 60% in optimal conditions. However, this high economic competitiveness is not consistent in more conservative operating scenarios. Furthermore, electrodialytic crystallization has 42% lower global warming potential than existing technologies. Scenario and sensitivity assessments completed in this chapter identify the operating parameters of electrodialytic crystallization that greatly affect economic and environmental impacts. Most notably, improvements to the cost and performance of ion exchange membranes will provide the highest benefit to electrodialytic crystallization competitiveness. With appropriate concentration of future research on these high-impact areas, the economic and environmental viability of electrodialytic crystallization should continue to increase in the coming years and electrodialytic crystallization will compete with existing zero liquid discharge technologies to provide a low-cost, efficient, and low-impact replacement to existing technologies. This chapter also shows the limited viability of membrane distillation with a crystallizer in replacing existing zero liquid discharge technologies due to high costs. In either case of electrical heating or waste heat use for membrane distillation, energy costs or infrastructure costs stemming from high energy intensity of membrane distillation result in costs far exceeding those of existing technologies. Through economic and environmental analysis expand the understanding of the potential for technologies to reach industrial application, further analysis can be leveraged to evaluate the fit of technologies into specific applications based on multiple stakeholder perspectives of the system needs. In the fifth chapter of this work, technology options were qualitatively evaluated under a stakeholder-informed triple bottom line sustainability perspective Chapter 5 of this work evaluates proposed technical solutions to produced water desalination and considers the additional economic, environmental, and social barriers that exist within the oil and gas industrial system. The consideration of these three impact areas (i.e., economic, environmental, and social) are defined as the triple bottom line considerations. The drivers, pressures, states, impacts and responses framework, first developed by the European Environmental Agency and later updated by the United States Environmental Protection Agency, was used to support the work of chapter 5 by organizing broad system considerations collected from stakeholder-generated literature into an orderly and approachable list of system indicators to evaluate technology compatibility within the applied system. System indicators are quantified, and overall system compatibility scores are calculated based on a variety of stakeholder preference scenarios. The results show that, given current models, emerging technologies have the potential to compete with existing zero liquid discharge technologies when applied to the oil and gas industry for produced water desalination under applications where stakeholders have low economic preference. Careful consideration of stakeholder preferences is necessary because technologies rank differently based on weightings of economic, environmental, and social impact importance. In summary, through thermodynamic and system modeling, techno-economic analysis, life cycle assessments, and triple bottom line sustainability considerations, four zero liquid discharge desalination technology options for the oil and gas industry (i.e., mechanical vapor compression with a crystallizer, electrodialytic crystallization, membrane distillation with a crystallizer using electrical heating, and membrane distillation with a crystallizer using waste heat) were evaluated for the Denver-Julesburg Basin in Northern Colorado. Overall, development of ion exchange membranes with improved performance for electrodialytic crystallization and developments in lowering membrane distillation energy intensity will determine the future economic competitiveness of electrodialytic crystallization and membrane distillation, respectively, as desalination technology options over mechanical vapor compression. However, when evaluating triple bottom line sustainability, results show potential for applications where there is lower preference to economic performance. In such applications, electrodialytic crystallization and membrane distillation with a crystallizer using waste heat consistently compete with mechanical vapor compression-based systems. Further understanding of the applied system needs and stakeholder preferences will determine overall applicability of technologies into the system.
Keywords: produced water treatment; triple bottom line sustainability; techno-economic analysis; life cycle assessment